Economic evaluation of a phase III international randomised controlled trial of very early mobilisation after stroke (AVERT). Issue 5 (22nd May 2019) - Gao, Lan; Sheppard, Lauren; Wu, Olivia; Churilov, Leonid; Mohebbi, Mohammadreza; Collier, Janice; Bernhardt, Julie; Ellery, Fiona; Dewey, Helen; Moodie, Marj
Abstract : Objectives: While very early mobilisation (VEM) intervention for stroke patients was shown not to be effective at 3 months, 12 month clinical and economical outcomes remain unknown. The aim was to assess cost-effectiveness of a VEM intervention within a phase III randomised controlled trial (RCT). Design: An economic evaluation alongside a RCT, and detailed resource use and cost analysis over 12 months post-acute stroke. Setting: Multi-country RCT involved 58 stroke centres. Participants: 2104 patients with acute stroke who were admitted to a stroke unit. Intervention: A very early rehabilitation intervention within 24 hours of stroke onset Methods: Cost-utility analyses were undertaken according to pre-specified protocol measuring VEM against usual care (UC) based on 12 month outcomes. The analysis was conducted using both health sector and societal perspectives. Unit costs were sourced from participating countries. Details on resource use (both health and non-health) were sourced from cost case report form. Dichotomised modified Rankin Scale (mRS) scores (0 to 2 vs 3 to 6) and quality adjusted-life years (QALYs) were used to compare the treatment effect of VEM and UC. The base case analysis was performed on an intention-to-treat basis and 95% CI for cost and QALYs were estimated by bootstrapping. Sensitivity analysis were conducted to examine the robustness of base case results. Results: VEM and UC groups were comparable in the quantity of resource use and cost of each component. There were no differences in the probability of achieving a favourable mRS outcome (0.030, 95% CI −0.022 to 0.082), QALYs (0.013, 95% CI −0.041 to 0.016) and cost (AUD1082, 95% CI -$2520 to $4685 from a health sector perspective or AUD102, 95% CI -$6907 to $7111, from a societal perspective including productivity cost). Sensitivity analysis achieved results with mostly overlapped CIs. Conclusions: VEM and UC were associated with comparable costs, mRS outcome and QALY gains at 12 months. Compared with to UC, VEM is unlikely to be cost-effective. The long-term data collection during the trial also informed resource use and cost of care post-acute stroke across five participating countries. Trial registration number: ACTRN12606000185561; Results.